ZNACZENIE EKSPORTU W TWORZENIU DOCHODU NARODOWEGO W PAŃSTWACH O RÓŻNYM POZIOMIE ROZWOJU GOSPODARCZEGO - Maćkowiak, Henryk (Wydział Prawa i Administracji UAM, 1998)
The aim o f the present study was: (1) co determine the effect o f selected factors on the contribution of exports to national income in states at various levels o f economic development, and (2) to show differences in the generation of national income by exports, and to give an explanation of those differences in the studied set of 127 countries. No confirmation was found of the common opinion about the generally positive correlation between the contribution of exports to national income and the level of economic development of a country. The contribution depends very often on different groups of factors, as was corroborated by a statistical estimation of the role of selected factors in the contribution of exports to the GDP. Eight explanatory variables were adopted: the Gross National Product of a country, per capita GNP, the area of the country, its population, the GNPs of the neighbouring states, the per capita GNPs of these states, their areas, and their populations. In advanced countries, the contribution of exports to national income was most closely associated with their population numbers and their economic potential. These variables turned out to be negatively correlated with the dependent variable. In less advanced countries, the contribution of exports to national income was most strongly dependent on their economic level. The role of exports in generating national income can be said to be highly diversified, and this refers to all countries, whether economically advanced, developing, or those in the process o f socioeconomic transformation. In the group of the most advanced countries, the exports o f the USA and Japan contribute the least to their national incomes. Although they are both leading exporters owing to their huge economic potential, their domestic markets are big enough to absorb a considerable proportion of industrial output. A big contribution of exports to national income is characteristic of small industrialised countries. What turned out to be a much harder task was accounting for differences in the income-generating capacity of exports in the group of countries at a lower level of economic development. If a country’s export structure is dominated by high-priced raw materials (e.g. oil), then as a rule the greater the contribution of exports to national income, the higher the country’s index of economic development. In those countries, in turn, which mainly export lower-priced minerals or raw materials of vegetable origin and barely processed farm produce, the exports play a smaller or altogether insignificant role in generating their GDPs; as a result, they have very low indices o f economic development. Owing to their specialised, export-oriented manufacturing policy, in the newly industrialised countries of South-Eastern Asia the share of exports in their GDPs is fairly high. Exports play a major role in generating the national income of the small states that came into being after the collapse o f the USSR (Estonia, Lithuania, Latvia, Azerbaijan), Czechoslovakia (the Czech Republic, Slovakia), and Yugoslavia (Slovenia, Croatia, Macedonia), where exports often contribute more than 50% to their GDPs.
THE SIGNIFICANCE OF EXPORTS IN THE GENERATION OF NATIONAL INCOME IN COUNTRIES AT VARIOUS LEVELS OF ECONOMIC DEVELOPMENT